2017
DOI: 10.1128/aac.02107-16
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-Mediated Mutagenesis Is Suppressed by Subinhibitory Concentrations of Amikacin in Pseudomonas aeruginosa

Abstract: Resistance to antibiotics is a global health problem. Activation of the SOS response, and the subsequent elevation in mutagenesis, contributes to the appearance of resistance mutations. Among currently used drugs, quinolones are the most potent inducers of the SOS response. In the present study, we show that amikacin inhibits ciprofloxacin-mediated SOS induction and mutagenesis in Pseudomonas aeruginosa.KEYWORDS Pseudomonas aeruginosa, SOS response, ciprofloxacin, recA A ntibiotics may cause genetic changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
3
21
1
4
Order By: Relevance
“…The following studies contain relevant data, but were excluded from the analysis despite matching our a priori inclusion criteria: Gutierrez et al [5], Schroder et al [36] (data available, but in a different representation or in a summary form); Kohanski et al [4], Nair et al [37], Peng et al [38], Bunnell et al [39], Cairns et al [40], Thi et al [41], Song et al [42], Valencia et al [43], Nagel et al [44] (raw data unavailable or no answer from the author who kept the raw data).…”
Section: Meta-analysis Of Previous Studiesmentioning
confidence: 99%
“…The following studies contain relevant data, but were excluded from the analysis despite matching our a priori inclusion criteria: Gutierrez et al [5], Schroder et al [36] (data available, but in a different representation or in a summary form); Kohanski et al [4], Nair et al [37], Peng et al [38], Bunnell et al [39], Cairns et al [40], Thi et al [41], Song et al [42], Valencia et al [43], Nagel et al [44] (raw data unavailable or no answer from the author who kept the raw data).…”
Section: Meta-analysis Of Previous Studiesmentioning
confidence: 99%
“…A change in cell morphology has been previously characterized as a survival mechanism of E. coli present in urinary tract infections (French, Cote, Stokes, Truant, & Brown, ; Justice, Hunstad, Cegelski, & Hultgren, ; Klein, Palarasah, Kolmos, Moller‐Jensen, & Andersen, ), and CIP‐induced filaments were found to give rise to antibiotic‐resistant populations (Bos et al, ). This survival mechanism is linked to pathway activation in response to DNA breaks, thus promoting error‐prone repair and driving evolution (Recacha et al, ; Torres‐Barcelo et al, ; Valencia, Esposito, Spira, Blazquez, & Galhardo, ). Further studies have identified that the coordination of DNA repair after DNA damage, arising from CIP in this study, can accurately predict the emergence of a persister phenotype (Mok & Brynildsen, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many mechanisms of resistance to quinolones and fluoroquinolones. However, sub-inhibitory concentrations of several antibiotics are known to induce SOS but not result directly in cell death [34,[74][75][76][77]]. Therefore we model the impact of phage induction on P. aeruginosa population size with and without antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Note that not all antibiotics induce phage [34], so we focus only on the types of antibiotics known to do so (e.g., quinolones like Levofloxacin and Ciprofloxacin) [8,73]. We assume that even antibiotic-resistant bacteria induce viruses in the presence of antibiotics, which has been demonstrated for several classes of antibiotics [34,[74][75][76][77].…”
Section: Antibioticsmentioning
confidence: 99%